2004
DOI: 10.1007/s00198-003-1577-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A intake and the risk of hip fracture in postmenopausal women: the Iowa Women?s Health Study

Abstract: Excessive intake of vitamin A is postulated to have a detrimental effect on bone by inducing osteoporosis. This may lead to an increased risk of fracture, particularly in persons who are already at risk of osteoporosis. However, few studies have specifically examined the association of vitamin A intake through diet and supplement use, with fractures in a cohort of older, community-dwelling women. We prospectively followed a cohort of 34,703 postmenopausal women from the Iowa Women's Health Study to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
117
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 29 publications
5
117
1
3
Order By: Relevance
“…According to multivariate analysis of data, retinol intake was negatively associated with BMD. According to a cox regression analysis the risk of fracture was found to be the highest among men with the highest levels of serum retinol in a population-based (2322 men, 49-51 years) longitudinal cohort study [22]. These results are consistent with the results reported from animal and epidemiologic dietary studies.…”
Section: Toxicological Implications Of Elevated Hepatic Storage Of VIsupporting
confidence: 85%
“…According to multivariate analysis of data, retinol intake was negatively associated with BMD. According to a cox regression analysis the risk of fracture was found to be the highest among men with the highest levels of serum retinol in a population-based (2322 men, 49-51 years) longitudinal cohort study [22]. These results are consistent with the results reported from animal and epidemiologic dietary studies.…”
Section: Toxicological Implications Of Elevated Hepatic Storage Of VIsupporting
confidence: 85%
“…It was shown that risk of hip fracture was 1.18 fold in vitamin A supplement users compared to nonusers (95% CI, 0.99 to 1.41), but there was not a greater risk of all fractures among the users of vitamin A supplement. 70 The importance of vitamin A in the bone remodeling process has been shown in various studies. Vitamin A deficiency results in retarded bone growth, but in the other hand hypervitaminosis A leads to accelerated bone resorption, bone fragility, and spontaneous fracture.…”
mentioning
confidence: 98%
“…(1)(2)(3)(4)(5)(6)(7)(8)(9)(10) Numerous case studies have shown that overt vitamin A toxicity is associated with increased bone resorption and hypercalcemia. (11)(12)(13) Some studies have found that higher dietary vitamin A intake may account for a component of fracture risk within the general population and that supplemental vitamin A may be harmful even within recommended limits.…”
mentioning
confidence: 99%
“…In marked contrast, two recent prospective studies found no association between dietary vitamin A intake and risk of fracture. (5,6) Only one prospective study (4) has addressed exposure to vitamin A using biochemical markers of retinol intake in relation to fracture risk. This cohort study (4) followed 2322 middle-aged Swedish men for 20 years and reported a 64% increase in risk of any osteoporotic fracture for men in the top quintile of serum retinol relative to those in the middle quintile.…”
mentioning
confidence: 99%